2008
DOI: 10.1097/ta.0b013e31818233ef
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotection and Lethality Rescue by Histone Deacetylase Inhibitor Valproic Acid in Fatal Hemorrhagic Shock

Abstract: VPA offers considerable protection in severe hemorrhagic shock. The role of HDAC inhibition is suggested in mediating prosurvival actions of VPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…We have shown previously that severe hemorrhage is associated with HDAC/HAT imbalance, which influences the acetylation status of cardiac, lung, and liver histones, and that it can be corrected by treatment with pharmacologic HDAC inhibitors (HDACI) [1][2][3][4][5]9]. In a rodent model of lethal hemorrhagic shock, we have recently reported that post-shock administration of HDACI, such as VPA or suberoylanilide hydroxamic acid, significantly improves survival even in the absence of conventional fluid resuscitation [4].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have shown previously that severe hemorrhage is associated with HDAC/HAT imbalance, which influences the acetylation status of cardiac, lung, and liver histones, and that it can be corrected by treatment with pharmacologic HDAC inhibitors (HDACI) [1][2][3][4][5]9]. In a rodent model of lethal hemorrhagic shock, we have recently reported that post-shock administration of HDACI, such as VPA or suberoylanilide hydroxamic acid, significantly improves survival even in the absence of conventional fluid resuscitation [4].…”
Section: Discussionmentioning
confidence: 98%
“…At a cellular level, hemorrhagic shock and resuscitation can alter gene expression and impair the regulation of subsequent downstream survival pathways. Histone proteins are known regulators of transcription, and we have previously shown that treatment with histone deacetylase inhibitors (HDACI) can enhance nuclear acetylation [1], promote gene transcription [2], attenuate organ injury [3], and improve survival [4] in animal models of lethal hemorrhage, even in the absence of fluid resuscitation. We have also shown that administration of HDACI can protect neurons from hypoxia-induced apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…One readily available and widely used agent is valproic acid (VPA, 2-propylpentanoic acid), an HDAC inhibitor. 11,12 Drugs that target histone acetyltransferases and HDAC activities may provide cytoprotective effects, resulting in less demand for aggressive resuscitative efforts, and could significantly improve outcome after hemorrhage. 12 Although established as a long-term treatment for epilepsy, bipolar disorders, migraine, and neuropathic pain, several in vitro models have demonstrated that VPA attenuates expression of angiogenic and vascular permeability factors.…”
mentioning
confidence: 99%
“…11,12 Drugs that target histone acetyltransferases and HDAC activities may provide cytoprotective effects, resulting in less demand for aggressive resuscitative efforts, and could significantly improve outcome after hemorrhage. 12 Although established as a long-term treatment for epilepsy, bipolar disorders, migraine, and neuropathic pain, several in vitro models have demonstrated that VPA attenuates expression of angiogenic and vascular permeability factors. 13 Many possible pathways exist in the etiologic benefit of VPA 13 ; however, it is likely that these actions are the result of HDAC inhibitor activity, causing histone hyperacetylation.…”
mentioning
confidence: 99%
“…Alternatively, treatment with VPA (an HDACI) induced acetylation of histones (H2A, H3, and H4), normalized serum levels of these enzymes and prolonged survival by fivefold. Furthermore, hyperacetylation of the histone proteins indicated the presence of active genes and correlated with improved survival (Gonzales et al 2008). Gene expression profiling data from our group has shown that VPA treatment up-regulates expression of 17 critical genes at the early stage of HS (Fukudome et al, unpublished data).…”
Section: Hdaci In Models Of Hemorrhagic Shockmentioning
confidence: 99%